2012
DOI: 10.1177/0192513x12466385
|View full text |Cite
|
Sign up to set email alerts
|

A Burden of Support? Household Structure and Economic Resources Among Mexican Immigrant Families

Abstract: The children of Mexican immigrants face formidable barriers to achieving socioeconomic mobility due to their parents' precarious economic position and high rates of unauthorized status. In the short term, Mexican immigrants often coreside in extended household living arrangements with extended kin and unrelated friends and associates to shelter themselves from economic deprivation and insecurity of unauthorized status. Using individual-level Census data, the present study examines how family economic resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…It has been reported that migrants of diverse origin are more likely to share households. On a similar note earlier studies have found that living arrangements of migrants differ compared to non-migrants in which the economy of scale has been suggested as one of the explanatory factors (Glick and Van Hook 2002;Goldscheider and Goldscheider 1989;Leach 2014). Changing economic conditions with more job insecurity and higher unemployment was, in line with this, shown to result in remaining in the parental home longer (Gauthier 2007).…”
Section: Introductionmentioning
confidence: 56%
“…It has been reported that migrants of diverse origin are more likely to share households. On a similar note earlier studies have found that living arrangements of migrants differ compared to non-migrants in which the economy of scale has been suggested as one of the explanatory factors (Glick and Van Hook 2002;Goldscheider and Goldscheider 1989;Leach 2014). Changing economic conditions with more job insecurity and higher unemployment was, in line with this, shown to result in remaining in the parental home longer (Gauthier 2007).…”
Section: Introductionmentioning
confidence: 56%
“…While most financial behavior research focuses on individuals, there has been some attention to financial socialization across generations (Chiteji & Stafford, 1999;Hellstrom et al, 2013;Keister, 2003;Leach, 2012;Li, 2009;Yorgason et al, 2011). There is a lack of information about how extended family members influence our financial decisions.…”
Section: Suggestions For Researchmentioning
confidence: 99%
“…Shared households are another form of resource pooling that includes multifamily households, as well as adult children and members who are not relatives or romantic partners (Mykyta & Macartney, ). Some households may include fictive kin (e.g., godfather/godmother) and nonkin (e.g., roommates) (Leach, ; Robles, ). In 2011, 22 million households were shared, and 41.2 million adults were sharing a household with adults who were not their spouse or romantic partner (Mykyta & Macartney, ).…”
Section: Types Of Extended and Shared Householdsmentioning
confidence: 99%
See 2 more Smart Citations